Co-creating value at Christmas: A study of portrayals of Christmas consumption in Women's Interest Magazines. - Howard, Christina (2010)
This study examined portrayals of Christmas consumption in ‘Good Housekeeping’, ‘SHE’, and ‘essentials’ magazines between 2003 and 2009. The objective of the research was to investigate the perspectives communicated by the magazines regarding consumer co-creation of value within the context of Christmas in the United Kingdom. This research was conducted within the social constructionist philosophy. A semiotic analysis of the magazine covers and qualitative content analysis of the data was undertaken. The data was categorized into codes through thorough examination, using an iterative process. The coding categories provided the basis of the insights gained as a result of the research. The studied magazines were revealed to provide consumers with information, inspiration and advice enabling them to co-create value in consumption activities throughout the festive season. Value co-creation opportunities were highlighted primarily as means of reducing stress and increasing enjoyment, as well as providing a method of lessening the financial burden of the Christmas period. By providing consumers with knowledge and alternative solutions, the magazines enable consumers to increase their skills and so co-create value with companies to meet their individual needs and abilities at this time. Therefore the likelihood of the consumers’ orchestrating a Christmas celebration with which they can be satisfied is increased by the magazines guidance.